Private affluence versus public squalor: attitudes towards recycling domestic waste. - Wilks, Daniela Carvalho (2008)
There has been, in recent years, substantial debate over environmental issues in the media and in schools, and one can by now assume the existence of at least minimal awareness on the part of the general public. One important aspect of the debate concerns the recycling of domestic waste, and European countries are expected to comply with European directives on this matter. However, there remains everywhere a mismatch between assumed public awareness and actual practice. This is certainly the case in Portugal where indicators show that levels of public participation in locally sponsored recycling initiatives are low. Given their higher levels of education, one might assume that university students show more awareness of environmental problems and are accordingly more active in contributing to solving them. In order to study the attitudes of Portuguese students towards recycling a questionnaire survey was conducted with a sample of 600 students in Portuguese universities. Data thus gathered so far seems to indicate that the majority of students are generally aware of the public importance of recycling and practice this in their private lives. Results are analysed in the light of the concept of social capital, and the paper theorises a connection between the levels of public participation in recycling and the prevalence (or not) of social capital in Portuguese society. It concludes by suggesting the most cost efficient allocation of resources to increase participation rates.